O Teorema do Ponto Fixo de Banach para Contrações e Algumas Aplicações. - Silva, Thiago Marques da (Universidade Federal do Tocantins, 2020)
This paper aims to address a brief concept of Metric Spaces in order to present and demonstrate Banach’s Fixed-Point Theorem in Euclidean Space-ndimensional R n . In addition, display some of its applications, especially in the demonstration of Existence and Uniqueness of Solutions of Ordinary Differential Equations. For this, we had to first study essential concepts such as the Topological Aspects of Space R n , Metric Spaces and Spaces Complete Metrics, in order to define Banach Spaces and then to enunciate, demonstrate and show some applications of the Banach’s Fixed-Point Theorem for contractions which tells us that if R n is a complete metric space, every contraction f : R n → R n has a single